Where is the T in LGBT? : exploring the links between the gay and lesbian rights movement and the transgender rights movement - Cooper, Krystal (Kansas State University, 2015)
Using a historical comparative analysis, this thesis explores the convergence and divergence of the gay and lesbian rights movement and the transgender rights movement. Historically, these movements have been closely related to each other. In the 1960s, the gay and lesbian rights movement and the transgender rights movement had very similar beginnings. However, the organizations that advocated for gay and lesbian rights marginalized the rights of transgender people, even though both movements were working against similar forms of oppression. While the gay and lesbian rights movement began to include transgender rights into organizations in the 1990s there were still indications that the needs of transgender people are not always met in the LGBT movement. The current steps in the LGBT movement have suggested an attempt to be more inclusive of the transgender rights movement, however there are still signs that the needs of more marginalized members of the LGBT movement are not being met. The thesis suggests an importance of coalition building in social movements to be more able to address intersecting forms of discrimination. It also explores how with diverging interests there is conflict in coalition building.
Keywords: Lesbian, Gay, Bisexual, and Transgender Rights Movement; Transgender Rights Movement; Sociology (0626)